Evaluasi Kinerja Pelayanan Publik di Nagari Pakan Sinayan: Menyelaraskan Ekspektasi Masyarakat dan Realita Pelayanan - Wahib Assyahri; Nurul Latifah (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
This study aims to evaluate public service performance in Nagari Pakan Sinayan by aligning community expectations with service realities. This research employs a quantitative approach using a survey method involving 100 respondents selected through simple random sampling to ensure data representativeness. A structured questionnaire that had undergone validity and reliability testing was used as the primary data collection instrument. The collected data were analyzed using simple linear regression through SPSS to determine the extent to which service quality contributes to community satisfaction. The findings show that service quality has a positive and significant effect on community satisfaction, as indicated by an Adjusted R² value of 31.3% and a significance level of 0.000, which falls below the 0.05 threshold. These results indicate that improvements in responsiveness, reliability, and empathy are essential elements in strengthening public trust and satisfaction with government services. The study concludes that enhancing the competence of nagari government officials and standardizing service procedures are strategic steps needed to align public service performance with community expectations